Simulation of soil moisture dynamics at different depth of soil profile - KUMAR, ROHITASHW; RASOOL, SHOWKAT; RAAZIA, SYEEDAH (Journal of Soil and Water Conservation, 2020)
The present study was conducted to evaluate non-linear model for multilayer vis-a-vis uniform root zone for maize crop in different agro-climate zone. Soil water dynamics of unsaturated soils is a function of soil water content, pressure head and hydraulic conductivity of soil. The governing moisture flow equation was solved using finite difference method and numerical simulation model was formulated coupling with 1D pressure head-based form of Richard’s equation with a non-linear root water uptake function. Constant flux as well as constant pressure head type boundary conditions were incorporated into the model. The model was validated with secondary level data for different boundary conditions and no root water uptake (uncropped soil) as well as with field data for a cropped soil. The model also takes into account the effect of plant root water uptake on the moisture profile of soil considering nonlinear extraction pattern of plant roots as given by the Ojha and Rai (O-R) root water uptake model. The model simulated moisture profiles were in good agreement with the observed moisture profiles of the unsaturated soils.